(untitled) (Revista horizonte, 2017)
The aim of the study was to verify the interference of stretching protocols on neuromuscular parameters. Materials and Methods: 15 healthy, physically active women participated in the study and were evaluated in the exercise of half squat, in the parameters: Maximum Isometric Voluntary Contraction (CVIM); Surface Electromyography (EMG) in the Vasto Medialis (VM), Vasto Lateralis (VF) and Rectus Femoris (RF) muscles, and the EMG/KGftotal ratio. The volunteers were subjected to a knee flexion stretch, and they were subjected to 4 stretching times of 0", 10", 30" and 60" seconds, respecting a randomization of the stretching times and an interval of 72 hours between each stretching time and the execution of the neuromuscular tests. The statistical analysis used the Shapiro Wilk test to verify the distribution of the sample and the Repeated Measures Anova to verify the behavior of the variables between the stretching stimuli. Results: It was not possible to identify significant differences in the CVIM between the support times. In the EMG variable, it was possible to identify significant differences in MV between SE and 30", and SE and 60", as well as 10" and 30". Conclusion: It can be concluded that the proposed stretching stimuli do not affect the neuromuscular parameters studied, but the stimuli in the 30 and 60 seconds seem to bring better results in strength. In the meantime, it is necessary to look for future proposals in which the stretching intensity is controlled, in order to know its effects on the neuromuscular quantifications.